INVESTMENT IN FIXED ASSETS LISTED IN INDONESIA STOCK EXCHANGE - Arnita, Vina (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
This study discusses the analysis of fixed assets investment in PT. Adi Sarana Armada Tbk. The purpose of this study is to determine the extent to which management of fixed assets on the rate of return on investment on PT Adi Sarana Armada Tbk, through its activities the company began from the way the acquisition of fixed assets, depreciation method, and measure the rate of turnover of a fixed asset during its use and analysis the return on investment (ROI) to assess how efficient performance company in utilizing total assets to obtain profit. The research method used by the author is quantitative descriptive. The Data analyzed in the study is secondary data obtained from the financial report of PT. Adi Sarana Armada Tbk listed on Bursa efek Indonesia (BEI) of the year 2012 until the year 2014. The results of the research are the acquisition of fixed assets secured by the loan's long-term credit. Depreciation using the straight-line method to total assets fixed. The straight-line depreciation method produces a depreciation expense higher so the impact on profits Company. Where be aware of the profit that is produced by PT. Adi Sarana Armada Tbk experiences a significant decline as a result of too large the administrative burden that is largely dominated by the load of the depreciation of the vehicle. in rent. Then investment against fixed assets not in balance with the increasing sales in a sufficient amount so that the lead fixed asset turnover also decreased ditahun2014. Conditions-conditions it contributed negatively to the rate of return investments decreased in 2014 as compared in the year 2013.